Tumor-Like Liver Abscess Mimicking Malignancy With Lung Metastases in a Patient With Acute Renal Failure: A Case Report. Issue 11 (March 2016) - Wang, Chih Hsin; Sun, Cheuk-Kay; Jiang, Jiunn-Song; Tsai, Ming Hsien
Abstract : Abstract: The worldwide incidence of Klebsiella pneumoniae liver abscess (KLA) is increasing. It is important to accurately diagnose this life-threatening disease to provide timely and appropriate treatment. Here we report the case of a 38-year-old man with acute renal failure and a tumor-like liver abscess and septic pulmonary embolism. Initially, his clinical symptoms, laboratory tests, and radiological findings presented equivocal results of malignancy with metastases. Fine needle aspiration of liver tumor was performed, which showed purulent material with a culture positive for K pneumoniae . KLA symptoms are atypical, and radiological findings may mimic a malignancy with tumor necrosis. In some circumstances, liver aspiration biopsy may be necessary to confirm the real etiology, leading to prompt and timely treatment. Moreover, we should be alert for the impression of KLA when facing a diabetic patient with liver mass lesion and acute renal failure.